Looking through landscapes of technology: Impact of virtual worlds in children's lives - Oliveira, A.; Dias, R.; Alturas, B. (Conflicts in childhood, 2014)
The new technologies are becoming more crucial in many areas of our lives. Everything that relates to technologies, telecommunications and information systems, may give us benefits, facilitating and speeding up many tasks, in a convenient way. Here, we highlight the impact of the virtual worlds in children’s lives and experiences, particularly, the role of computers in learning - as an essential tool that also facilitates interactivity between teachers and students. (The technological innovations can also be poorly used, due to ignorance or perversity, for instance, to disseminate misleading information or private images, online). We conducted an exploratory study, with a population of boys and girls, between 9 and 11 years old, attending the fourth year of schooling. We intended to verify the importance that children give to the computer in their personal, social and cognitive development - and how they use this technology, daily. The main goal was to identify the perceptions of children in relation to the importance of the computer in their learning, and in their lives. Most children said that can't live without the computer, emphasizing the help it gives them, mainly by the possibility to research on the internet, where they can learn, find help for their homework, and access (so often with no control) to information previously unknown. They also like to feel connected to friends. Children associate the use of computer with intelligence, because through it they can answer to questions and have access to information about everything happening on the world. Girls use the computer especially to perform research or homework, and to talk with friends, while boys use the computer mainly for entertainment and gaming (including online games). Children surf in the virtual worlds with ease and practical sense, searching for knowledge, emotions and experience. Yet, they run risks, especially in social networks (like Facebook).